Features of the institution of complicity in criminal legislation of the Republic of Bulgaria and the Republic of Kazakhstan: comparative analysis - Abdukarimova З.Т.; Turgynbek Г.Р.; Rzabay А.И. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2025)
This article examines the characteristics of complicity in the criminal legal systems of Bulgaria and Kazakhstan, identifying similarities as well as differences in how roles and responsibilities of accomplices are defined and distributed. In comparing the legal framework of these two countries, the authors hypothesize that despite their different legal traditions and historical contexts, both countries face common problems in regulating the responsibility of those involved in crimes, by more than one person. The methodology of the study includes a comparative analysis of the penal codes of both countries using existing law and doctrinal sources to assess how each legal system qualifies the institution of complicity. The results highlight that although both legal systems share common conceptual frameworks, such as recognition of different roles and personal punishment of accomplices, approaches differ in their application. Kazakhstan’s legal framework tends to emphasize more detailed role classification, while Bulgaria has a more flexible, context-dependent approach to defining the responsibility of accomplices. The article contributes to academic debate by offering a clearer understanding of how legal systems govern participation and accountability, while emphasizing the practical implications of this framework for achieving fair and individualized justice. This study not only broadens our understanding of complicity and its application in criminal law, but also offers recommendations for improving the clarity and consistency of legal classifications.